Delimitation of management zones for macronutrients in coffee crop conilon intercropping with rubber trees - Oliveira de Jesus Santos, Eduardo; Barreto Pinto, Flávia; de Almeida Barbosa, Marina; Gontijo, Ivoney (Coffee Science - ISSN 1984-3909, 2015)
Studies on the determination of management zones and the spatial variation of attributes associated with yield response of crops soil can contribute to the rational application of inputs, enabling economic and environmental gains. The purpose of this study was to determine the spatial distribution of soil macronutrients Ca, Mg, K and P and defining management zone for application of inputs in a conilon crop intercropped with rubber, using the technique of cluster analysis. The study was conducted in the Nova Venecia, municipality of Espírito Santo, state Brazil. The experimental area has dimensions of 24 x 63m (1.512m2) and embossed with convex shape, where we marked a grid of 60 sampling points. At each sample point were collected four replicates of soil in the projection of the coffee canopy, forming a sample at a depth of 0-0,20 m. Also collected one comprises the traditional method of sampling pathway zigzag sample was composed of 15 subsample. The results obtained were subjected to multivariate exploratory analysis: hierarchical clustering, according to the Ward’s method, in order to set the number of groups or management zones. The data were subjected to geostatistical analysis. In the dendrogram obtained with the technique of cluster analysis, three separate groups or management zones. The integrated cluster analysis with the characterization of the spatial variability of soil attributes was effective in defining areas of study in the plantation managements.